2017
DOI: 10.21037/cdt.2017.05.10
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between total ischemic time and mortality in patients with STEMI: every second counts

Abstract: We read with great interest the recently published article in the October 2016 issue of JACC Cardiovasc Interv by Rashid et al. (1). Briefly, it was a retrospective, single center study that analyzed ST-elevation myocardial infarction (STEMI) patients with symptom onset <12 hours. Patients with primary percutaneous intervention (PCI) were compared with those who received fibrinolytic therapy prior to arrival at the hospital due to non-availability of primary PCI. The authors concluded that the pharmaco-invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 21 publications
1
15
0
2
Order By: Relevance
“…The results obtained in our study demonstrated the effect of the total time of hospitalization of patients on mortality in patients with AMI. This confirms the findings of a number of previous studies, in which the total time of myocardial ischemia was also an important predictor of death both in the hospital and in the long-term period [15,16].…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained in our study demonstrated the effect of the total time of hospitalization of patients on mortality in patients with AMI. This confirms the findings of a number of previous studies, in which the total time of myocardial ischemia was also an important predictor of death both in the hospital and in the long-term period [15,16].…”
Section: Discussionsupporting
confidence: 91%
“…However, in re-cent years, new data and new treatment and diagnostic approaches have emerged that allow more successful treatment of patients with ACS [1,13]. Today, the importance of early contact of the patient with a health worker and the beginning of reperfusion therapy is not in doubt [2,8]. That is why the effective organization of treatment, close interaction of prehospital and subsequent stages of medical care becomes especially important.…”
Section: Discussion Of Research Resultsmentioning
confidence: 99%
“…The influence of various factors on the course and prognosis in patients with acute coronary syndrome (ACS) with ST segment elevation has been proven [1,2]. Such factors include demographic indicators, such as gender, age [3], anamnesis data (death of parents from heart disease, self-administration of antianginal drugs [3,4], hemodynamic parameters), blood pressure, heart rate [5,6], etiology and pathogenesis (nature of coronary artery occlusion, severity of coronary artery disease) [7], time factors (therapeutic window up to 12 h from the moment of clinical symptoms of the disease or a time interval up to 24 h from the moment of development of the clinical picture of ACS for percutaneous coronary interventions (PCI) [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It is well established that the time of presentation of STEMI from the onset of chest pain and timely treatment determines prognosis of patient. [11][12][13][14][15] For a number of reasons the time between emergency room (ER) arrival and symptom onset was the primary concern among the cardiologists and efforts have made it possible to brought it down to less than 90 minutes of recommended cutoff in most of the situations. 10,16 However, up until recent years the scientific community was less attentive towards the pre-hospital delays.…”
Section: Introductionmentioning
confidence: 99%